(untitled) (PERcursos Linguísticos, 2020)
This article is an excerpt from the master’s thesis, addressing questions about hate speech against the female fat body in the digital media Instagram, in addition to showing how women resist through their bodies. We use the Discourse Analysis of French tradition as the method of analysis, more specifically the archegenealogical method of discourse, in which the dialogues are constructed, especially, by the works of Foucault and Pechêux. At first, we approach the theory of our work, rescuing the history of AD and some categories of analysis, and we approach a little of the history of the discursivized female body through a descriptive and bibliographic research, analyzing, describing and interpreting the corpus. As a result, we realize that the female fat body still goes through several problems in society and this is mainly due to the hate speeches that predominate over their bodies and interconnected through the stereotypes created. Even so, the media, specifically the digital one, shows how these bodies can and should still show empowerment and resistance. Keywords: Fat female body. Hate speeches. Instagram. Resistance.